EVALUASI PROSES PENGANGGARAN DANA BANTUAN OPERASIONAL SEKOLAH DI KABUPATEN PURWOREJO - Rusmiyatun _ Rusmiyatun (FE Program Studi Manajemen, 2021)
This study aims to evaluate the budgeting process for School Operational Assistance Funds in Purworejo Regency. Evaluation measurement uses indicators issued by the United Nations Development Program (UNDP) on Good Governance with Transparency and Accountability variables in the Budgeting Process in Purworejo Regency. The samples of this study were 477 schools in Purworejo Regency and the BOS Management Team in Purworejo Regency in the Education, Youth and Sports Office of Purworejo Regency. The results showed that in general the implementation of the principles of good governance for accountability had been carried out well and met the principles of accountability. Even the overall Performance Accountability Score of Purworejo Regency gets a performance score of AA (Very satisfying). Meanwhile, for the Transparency Principle as measured by the legal framework, the availability of public information, open plan planning, implementation and reporting have been carried out quite well, but several schools still do not comply with the transparency of openness in the reporting sector. there are still 26,7% of schools that have not reported online on the Ministry of Education and Culture's website.Keywords: Good Governance, Accountability, Transparency, Purworejo Regency, Budget, BOS Funds.